Neoadjuvant Systemic Therapy: Promising Experimental Model or Improved Standard of Care? - Rizzo, Toni (MD Conference Express, 2013)
Neoadjuvant therapy (preoperative and primary systemic chemotherapy) was originally developed to improve management of patients with locally advanced breast cancer, in the hope that it would render inoperable disease operable. In 1988 results from the first longitudinal series of stage III breast cancer patients treated with this approach were published. Importantly, this landmark study also suggested that tumor response to neoadjuvant chemotherapy correlated well with patients’ overall survival. This article discusses the development of neoadjuvant therapy for patients with breast cancer, summarizing past experiences and reviewing its current use as a therapeutic research tool.